Flora predominante y producción de miel de abejas (Apis Mellifera) en tres localidades del cantón Chone - Alcívar Loor, Lilibeth Alexandra (2020)
This research is aimed at defining the predominant flora, the production and quality of bee honey in three localities of the Canton Chone. Area 1: Eloy Alfaro (common flora); area 2: San Antonio (lemon flora); area 3: Ricaurte (pitahaya flora). Observations were made on three beehives per zone, with a population of 25,000 to 30,000 bees. The relationship between season and flowering of the crops was observed and honey production was obtained, closed in time, in the three places. After the harvest, the quantity was recorded, and the quality of the honey was determined. ANOVA was applied to the amount of honey produced by area. The results showed that there were no significant differences at zone level. Physical-chemical tests (humidity, ash, sugar content, density, brix degree, pH) and microbiological tests (fungi and yeasts) were carried out to determine quality. Results showed normality in the 3 zones. An organoleptic test of acceptability was carried out, organized using a Likert scale and the Chi2 analysis showed that there were no differences in the organoleptic characteristics between the areas, with high acceptance of honey. It is concluded that vegetations with melliferous properties such as common flora, lemon cultivation and pitahaya cultivation predominate in the area of study and that they maintain similar volumes of production and quality of honey from bees. Because of the continuous flowering of the common flora, there is a tendency (P<0.10) to slightly increase production.